A survey on modeling guidelines for quantity takeoff-oriented BIM-based design - Monteiro, André; Poças Martins, João (Automation in construction, 2013)
While automatic Building Information Modeling (BIM) based quantity takeoff is one of the potentially most important and profitable applications for BIM, it is still generally underexplored how BIM models respond when quantity takeoff is its primary use. This article explores the subject by presenting a case study that surveys BIM input/output dynamics for quantity takeoff, examining model behavior when constrained by existing specifications for quantity takeoff, and detailing modeling guidelines that allow the user to extract quantities according to current specifications. The authors conclude that while it is possible to adapt the model to extract quantities according to existing specifications for manual-based measurements, the adjustments are not without its implications in other model applications such as visualization or drawings. Takeoff specifications should therefore be revised in order to account for BIM's features, and thus minimizing its limitations. •Importance of quantity takeoff for the project cost estimation.•There are several limitations about the application of BIM-based quantity takeoff.•Conflicts in the exchange of BIM-based quantity takeoff data.•BIM modeling must be adapted for quantity takeoff.•Modeling guidelines for BIM-based quantity takeoff.